UNIVERSITY COSTS OF GOVERNMENT CONTRACTS. - Smith, Frank P. (The Accounting Review, 1948)
Abstract The Statement of Principles provides a guide for determining costs of research and development contracts. It should assist in both the formulation and the administration of such contracts and should help representatives of educational institutions as well as personnel of the Army and the Navy. This guide should prove to be extremely helpful in the drafting of contracts since it points up specifically which types of costs customarily require contract authorization and which costs are reasonably assignable to the contract in the absence of prohibitive or permissive provisions in the contract. The Statement of Principles should facilitate the drafting of contracts which will be coordinated with the intentions, suggestions and words of warning included in the Statement of Principles. The principal contribution of the Statement of Principles will be in relation to indirect expenses. No single document of this type can settle, in advance of actual performance, all of the questions which will arise regarding expenses to be prorated and the most equitable methods of prorating such expenses. However, the Statement of Principles does bring to a conclusion many points which have caused endless discussion and prolonged negotiation in the past. Some of these points have been resolved in a highly arbitrary manner; nevertheless, here are special answers which appear to be generally practicable. The Statement of Principles is stated for the most part in accounting terms and has been built around accounts and accounting categories of expenses and costs. However, it is not an accounting document, and should not be considered as such. It is a realistic and matter-of-fact survey of the types of costs encountered in the performance of a research or development contract for the Army or the Navy by an educational institution.